Impact of Corrugated Fins on Flow and Heat Transfer Performance in Medium-Deep Coaxial Underground Heat Exchangers - Yan Shi; Chengcheng Liu; Hongxu Chen; Yaoshuai Yue; Mingqi Li (Energies)
To enhance the efficient development of geothermal energy, this study investigates the heat transfer enhancement mechanisms in medium-depth coaxial underground heat exchangers (CUHEs) integrated with corrugated fins, using computational fluid dynamics (CFD) simulations. Nine distinct corrugated fin geometries were modeled, and the streamlines, velocity fields, temperature fields, and turbulent kinetic energy were analyzed across Reynolds numbers (Re) ranging from 12,000 to 42,000. The results demonstrate that corrugated fins significantly promote fluid turbulence and mixing, thereby augmenting convective heat transfer. Compared to smooth inner tubes, the Nusselt number (Nu) is enhanced by a factor of 1.43–2.19, while the friction factor (f) increases by a factor of 2.94–6.79. The performance evaluation criterion (PEC) improves with increasing fin width and decreasing fin spacing. The optimal configuration, featuring a fin width of 15 mm, a spacing of 60 mm, and a thickness of 15 mm, achieves a maximum PEC value of 1.34 at Re = 12,000, indicating a substantial improvement in heat transfer performance within acceptable pressure drop limits. This research innovatively explores the performance enhancement of CUHEs at high Re, systematically elucidates the influence of geometric parameters on heat transfer and flow resistance, and employs the PEC index to optimize the structural design. This provides significant theoretical support for the efficient engineering application of CUHEs in geothermal utilization.